Cadherin-12 Regulates Neurite Outgrowth Through the PKA/Rac1/Cdc42 Pathway in Cortical Neurons - Guo, Beibei; Qi, Mengwei; Huang, Shuai; Zhuo, Run; Zhang, Wenxue; Zhang, Yufang; Xu, Man; Liu, Mei; Guan, Tuchen; Liu, Yan (Frontiers in Cell and Developmental Biology, 2021)
Cadherins play an important role in tissue homeostasis, as they are responsible for cell-cell adhesion during embryogenesis, tissue morphogenesis, and differentiation. In this study, we identified Cadherin-12 (CDH12), which encodes a type II classical cadherin, as a gene to promote neurite outgrowth in a vitro model consist of neurons with differentiated intrinsic growth ability. First, the effects of CDH12 on neurons were evaluated by RNA interference, and the result indicated that the knock down of CDH12 expression restrained the axon extension of E18 neurons. The transcriptome profile of the neurons with or without siCDH12 treatment revealed a set of pathways positively correlated with the effect of CDH12 on neurite outgrowth. We further revealed that CDH12 affected Rac1/Cdc42 phosphorylation in PKA dependent manner by testing with H-89 and 8-Bromo-cAMP sodium salt. Moreover, we investigated the expression of CDH12 in brain, spinal cord, and dorsal root ganglion during development by using immunofluorescence staining. Thereafter, we explored the effects of CDH12 on neurite outgrowth in vivo. A zebrafish model of CDH12 knockdown was established by using NgAgo-gDNA system and registered the vital role of CDH12 in peripheral neurogenesis. In summary, our study is the first to report the effect of CDH12 on axonal extension in vitro and in vivo and we provided a preliminary explanation for the mechanism.